Substitute Heirs in the Compilation of Islamic Law: An Overview from Gender Equality Perspective Case Study of the Religious Courts in Banjarmasin - Ideham, Wahidah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
The enactment of Article 185 of the Kompilasi Hukum Islam, solely translated as Compilation of Islamic Law) in Indonesia has brought some “winds of change” for the grandchildren whose parents (male or female) have died before the heirs. However, in the case of its application in the Banjar Muslim community of South Kalimantan, it seems that it still requires various efforts, such as subpoenas, lawsuits, requests through authorized institutions, and the assistance of advocates. This Article on Inheritance is indeed very brief, thus allowing for a juridical interpretation and opening opportunities for legal discretion against it. Therefore, different responses to it are necessary, and many perspectives can be considered to convey a conclusion and verify that the resolution of this case is by the principles of maqâshid al-syarîah—which are gender equitable—and benefit the family lineage. The Banjarmasin Religious Court, one of the institutions holding the authority to examine and adjudicate this inheritance issue, has issued its legal products in court decisions and verdicts. This research aimed to determine (1) how the case of substitute heirs in the Banjar community of South Kalimantan is resolved and (2) the application of Article 185 KHI in the Banjarmasin Religious Court. On this basis, a case study of several copies of the letter was the approach employed in this normative legal research. The study found that there were four decisions and two verdicts—which were all aligned with Article 185 of KHI and were gender-responsive.